Structure, Reactivity, and Mechanical Properties of Sustainable Geopolymer Material: A Reactive Molecular Dynamics Study - Li, Zhipeng; Zhang, Jinglin; Wang, Muhan (Frontiers in Materials, 2020)
Sodium aluminosilicate hydrate (NASH) gel, the primary binding phase in geopolymer, determines the mechanical properties and durability of environment-friendly construction materials. In this work, the models of NASH gel were obtained by two-step procedure: the temperature quenching method and Grand Canonical Monte Carlo water adsorption. The reactive force field molecular dynamics was utilized to investigate the structure, reactivity and mechanical performance of the NASH gel with Na/Al ratio ranging from 1 to 3. Q species, the connectivity factor, shows that the increase of sodium content in NASH gel leads to depolymerization of aluminosilicate network and more non-bridging oxygen atoms. The adsorbed water molecules dissociate near the non-bridging oxygen with high reactivity in defective aluminosilicate structure. The newly produced hydroxyls associate with the aluminate species, contributing to formation of pentahedron local structure. The sodium ions distributed in the cavity of the aluminosilicate skeleton have around 4 7 nearest neighbors. Furthermore, with increasing the amount of sodium, the molecular structure of the aluminosilicate skeleton is transformed from an integrity network to partial destroyed branch structures, which gradually decreases the stiffness and cohesive force of NASH gel characterized by the uniaxial tensile testing. During the large tensile deformation process, the reactive force field MD correlates the mechanical response with the chemical reaction pathway. The aluminosilicate skeleton is stretched broken to resist the tensile loading and the hydrolytic reaction of water molecules near the stretched Si-O and Al-O bond further accelerates the degradation of NASH gel. Hopefully, this work can shed light on material design for the high performance of sustainable geopolymer at nanoscale.